Raw spectra data alongside derived concentrations from the Cataract Scout Park, Australia, taken during the COALA-2020 campaign - Malcolm Possell; Danica Parnell; Alex Guenther; Jhonathan Ramirez-Gamboa; Hamish McDougall; Clare Paton-Walsh; Jack B Simmons (PANGAEA, 2022)
Raw spectra data in .cdf format alongside derived concentrations from the Cataract Scout Park, Australia, taken during the COALA-2020 campaign.